350 solved electrical engineering problems - EDWARD KARALIS (Engineering Press, 2000)
The book provides a concise review of the fundamental concepts of electrical engineering. This is accomplished with the problems chosen from the following seven areas of electrical engineering: direct and alternating current circiuts theory; linear and nonlinear electronics; classical and modern control systems; signal and systems communications; static and dynamic electromagnetic fields; power transmission and devices; combinational and sequential digital logic